Full scale deflection of ice by an icebreaker - Gagnon, R. E.; Spencer, D. (1993)
Two methods have been used to measure the full scale deflection of ice by the operation of the Canadian Coast Guard icebreaker, Sir John Franklin. The data show consistency and indicate that three types of disturbances were caused by the operation of the icebreaker in water with a .5 m ice cover. One type, long period water/ice waves (period ~5 s) caused by jamming of the ice sheet near the ship's maximum beam, may be associated with reports of structural damage of icebreakers that occurs in the vicinity of the 'shoulder' of the bow. The frequency of the jamming events and the magnitude of the ice deflection near the bow of the ship increase with ship speed. Peer reviewed: Yes NRC publication: Yes